1995
DOI: 10.1103/physrevlett.75.3130
|View full text |Cite
|
Sign up to set email alerts
|

Areal Density Measurement of Imploded Cryogenic Target by Energy Peak Shift of DD-Produced Protons

Abstract: DD-produced protons are used to measure the imploded fuel-shell areal density pAR. Twelve green beams of the GEKKO XII laser directly imploded a cryogenic foam-shell target containing a liquid or solid D2 fuel. The proton emission is detected through a dipole magnet on a CR-39 plate, whose energy shift from 3.02 MeV yielded the maximum pAR of 10 mg/cm' or the density of 6 g/cm', in agreement with that from the secondary neutron method within a factor of 2. The proton energy spread is sensitive to the laser ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…1. [13][14][15] Since the tantalum filter stops both carbon ions of less than 10 MeV and protons less than 1 MeV, 16 almost all the tracks on the CR-39 films will be from protons. Figures 2͑a͒-2͑d͒ show the proton tracks on four layered films from a 5 m thick target after 4 h etching and Figs.…”
Section: Proton Spectrummentioning
confidence: 99%
“…1. [13][14][15] Since the tantalum filter stops both carbon ions of less than 10 MeV and protons less than 1 MeV, 16 almost all the tracks on the CR-39 films will be from protons. Figures 2͑a͒-2͑d͒ show the proton tracks on four layered films from a 5 m thick target after 4 h etching and Figs.…”
Section: Proton Spectrummentioning
confidence: 99%
“…The compressed shell was completely opaque at peak compression. In the early 1990s, Nakai et al, 311 Tanaka et al, 312 and Kitagawa et al 313 reported implosions of cryogenic foam targets wetted with liquid deuterium. Typical targets were 10-lm-thick, 500-to 700-lm-diam foam shells coated with a 4-lm plastic ablator.…”
Section: B Cryogenic Implosionsmentioning
confidence: 99%
“…The two-step process can be described by Equations (2)-(4). The bulk etching depth can be calculated by Equation (5). With Equations (2)- (5), the track profile is obtained, shown as the solid line in Figure 1(a).…”
Section: Simulation Of the Track Profile Induced By A Charged Particlementioning
confidence: 99%